1995
DOI: 10.1038/bjc.1995.382
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of drug sensitivity of human malignancies by epidermal growth factor

Abstract: Summary We have previously show-n that epidermal growxth factor (EGF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…It is possible, therefore, that reduced DNA damage in these cells leads to less reactive oxygen species production. Both the involvement of growth factor receptor signaling pathways in mediating ERK activation by CDDP, and the importance of ERK in mediating CDDP-induced apoptosis, are consistent with two earlier reports indicating that EGF receptor activity can influence the response to CDDP (45,46). EGF stimulation was …”
Section: Fig 5 Roles For Jnk and P38 In Regulating Cddp-induced Aposupporting
confidence: 77%
See 1 more Smart Citation
“…It is possible, therefore, that reduced DNA damage in these cells leads to less reactive oxygen species production. Both the involvement of growth factor receptor signaling pathways in mediating ERK activation by CDDP, and the importance of ERK in mediating CDDP-induced apoptosis, are consistent with two earlier reports indicating that EGF receptor activity can influence the response to CDDP (45,46). EGF stimulation was …”
Section: Fig 5 Roles For Jnk and P38 In Regulating Cddp-induced Aposupporting
confidence: 77%
“…found to enhance the sensitivity of a variety of cancer cell types to CDDP (45), while down-regulation of EGF receptor expression by antisense RNA was correlated with enhanced resistance of breast cancer cells to CDDP (46). Overexpression of Ras also enhances sensitivity to CDDP, whereas inhibition of Ras correlates with resistance (21,22).…”
Section: Fig 12mentioning
confidence: 99%
“…Activation and elevation of EGFR have been shown to sensitize human cancer cells of breast, ovary, head and neck, cervix, colon, pancreas and prostate, as well as NSCLC to several classes of anticancer agents, including cisplatin and carboplatin, 5-fluorouracil, melphalan, and taxo1. [31][32][33] The modulating effect of epidermal growth factor (EGF) on anticancer agents has been demonstrated to be dependent on the number of EGFR and associated with downregulation of a form of DNA repair or inhibition of this activity. 32,33) In contrast, several reports have demonstrated that elevation of EGFR levels in human breast cancer cells might lead to increased chemoresistance to doxorubicin, vinblastine, and cisplatin, as well as 5-fluorouracil.…”
mentioning
confidence: 99%
“…Kroning et al (1995) showed the improvement of drug sensitivity including CDDP and 5-fluorouracil by EGF in various cell lines. Furthermore, they described that enhancement of drug sensitivity depended on the Figure 1 Scattergram showing relative c-erbB-2 mRNA expression levels (T/N: ratio of tumour to normal tissue) in relation to minor and major histopathologic response in resected specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In tumour cell lines, the sensitivity to several chemotherapeutic agents (Kroning et al, 1995;Dixit et al, 1997;Nouri et al, 2000) and radiotherapy (Kwok and Sutherland, 1989;Bonner et al, 2002) was significantly modified by EGF or EGFR expression levels. In addition, there is evidence that blocking EGFR could further increase chemo-and radiosensitivity of tumour cells expressing high receptor levels in vitro and in vivo (Anderson and Jankowski, 2003;Gee and Nicholson, 2003).…”
mentioning
confidence: 99%